Should modulation of p50 be a therapeutic target in the critically ill?. Issue 5 (4th May 2017) - Srinivasan, Amudan J.; Morkane, Clare; Martin, Daniel S.; Welsby, Ian J.
ABSTRACT: Introduction : A defining feature of human hemoglobin is its oxygen binding affinity, quantified by the partial pressure of oxygen at which hemoglobin is 50% saturated (p50), and the variability of this parameter over a range of physiological and environmental states. Modulation of this property of hemoglobin can directly affect the degree of peripheral oxygen offloading and tissue oxygenation. Areas covered : This review summarizes the role of hemoglobin oxygen affinity in normal and abnormal physiology and discusses the current state of the literature regarding artificial modulation of p50. Hypoxic tumors, sickle cell disease, heart failure, and transfusion medicine are discussed in the context of recent advances in hemoglobin oxygen affinity manipulation. Expert commentary : Of particular clinical interest is the possibility of maintaining adequate end-organ oxygen availability in patients with anemia or compromised cardiac function via an increase in systemic p50. This increase in systemic p50 can be achieved with small molecule drugs or a packed red blood cell unit processing variant called rejuvenation, and human trials are needed to better understand the potential clinical benefits to modulating p50.